Synthesis, Characterization and Biological Studies of Bisμ-2,2’-[N,N’-diylbis (nitrilomethylidyne)]diphenolatodicobalt(II) Using Triple Component Solvent System - Pervaiz, Muhammad; Yousaf, Muhammad; Jabbar, Abdul; Fawad Zahoor, Ameer; Hussain Bokhari, Tanveer; Anjum, Anbreen; Sagir, Muhammad; Ain Khan, Misbahul; Ghulam Ali, Kulsoom; Ahmad, Sajjad; et al. (Asian Journal of Chemistry, 2012)
The crystal structure of compound [Co2(C14H12N2O2)2] showed dimeric complex. Two nitrogen atoms and two oxygen atoms of the [N,N-bis(salicylidine)diamine] formed distorted square pyramidal geometry in the region of Co(II) and one oxygen atom from each ligand acting as bridge between two ligand molecules which are distorted in parallel path among each other. The titled complex showed amorphous crystalline structure in toluene solvent but to get more clear X-ray crystallographic data three component solvent system (ethanol, toluene, ethyl acetate) was used. The ligand was synthesized and characterized by FTIR, Mass spectrometry, NMR while the titled complex was characterized by FTIR and X-ray crystallography. The ligand and complex were screened for their antibacterial activity against bacterial species Escheria coli, Staphylococcus aureus and Bacillus subtilis and antifungal activity against A. flavus, A. alternate and A. niger. The activity data shows that the metal complex has more antibacterial and antifungal activities than the synthesized ligand against bacterial strains.